11 The Mammalian STE20-Like Kinase 2 (MST2) Modulates Pathological Hypertrophy by Activating the Proto-Oncogene RAF1. (20th November 2012) - Zi, M; Prehar, S; Maqsood, A; Reynolds-Khan, Y; Neyses, L; Cartwright, E; Oceandy, D
Abstract : The novel idea that the molecular regulation of cardiac hypertrophy is closely related to tumour/cancer growth has emerged recently. One key finding was the identification of tumour suppressor RASSF1A as a powerful inhibitor of pathological hypertrophy. The mammalian STE20-like kinase 2 (Mst2) forms a molecular complex with RASSF1A and is also implicated in the development of various tumours. In contrast to Mst1, the role of Mst2 in the heart has not been precisely elucidated. We used Mst2 knockout mice and isolated neonatal rat cardiomyocytes (NRCM) with an adenoviral mediated overexpression of Mst2 to investigate the role of Mst2 in the heart. Mst2-/- mice exhibited a significant reduction of hypertrophy in response to transverse aortic constriction (30% elevation in heart weight/tibia length ratio in Mst2-/- mice compared to 50% in wild type (WT), n=8, P<0.05). In agreement with the in vivo data, overexpression of Mst2 in NRCM significantly enhanced phenylephrine-induced cellular hypertrophy as indicated by cell size measurements and expression of the hypertrophic marker BNP. Since Mst2 physically interacts with Raf1, we investigated the activation of Raf1 and its downstream effector ERK1/2 in NRCM. Overexpression of Mst2 significantly increased the activation of Raf1 and ERK1/2 indicating that Mst2 positively regulates the pro-hypertrophic and pro cancer Raf1-ERK1/2 pathway. In conclusion, our data provide a key evidence of novel role of Mst2 as a positive regulator of cardiac hypertrophy by modulating the Raf1-ERK1/2 pathway. It also reinforces the notion that genes that are implicated in tumour growth/cancer are also important in myocardial hypertrophy.